Development of Merdeka Curriculum Teaching Materials by Using the Kvisoft Flipbook Maker Application to Improve Student’s Competence Class IV In Elementary School - Niki Yulianti; Yeni Erita; Yanti Fitria; Muhammadi (Postgraduate, University of Mataram, 2023)
A legitimate, useful, and productive theme learning teaching resource for the autonomous curriculum is what this research aims to provide. Utilizing the flipbook maker software from Kvisoft, this instructional material was created. Research and development (R&D) is the research methodology employed in this study. In this study, researchers used the ADDIE approach, which stands for analysis, design, development, implementation, and evaluation. Students in class IV of Elemntary School 03 Limo Badak, Malalak District, during the odd semester of 2022/2023 served as the study's test subjects. Validity analysis, practicality analysis, and analysis of the efficacy of instructional materials are the three types of data analysis that are used. Three conclusions can be drawn from the findings of the research and debate that have been done. The Kvisoft Flipbook Maker application can be used to create valid and usable educational materials in the form of e-books. Second, this instructional material proved to be useful and appropriate for usage in a good category. Third, the knowledge competency of elementary school pupils in the fourth grade can be effectively increased by using these instructional resources.